Traumatic Spondyloptosis Causing Complete Transaction of Spinal Cord - Yadav, Abhay; Sharma, Sashmit (Nepal Orthopaedic Association Journal, 2014)
Traumatic spondyloptosis is a rare presentation and is usually due to very high energy trauma. It is accompanied with cord injury, mostly complete transaction of the cord. In managing such cases special consideration should be given to soft tissues, surrounding structures and organs in the traumatized area. We present a case of traumatic spondyloptosis of D12/L1 in a middle aged gentleman with complete cord transaction. DOI: http://dx.doi.org/10.3126/noaj.v3i2.9527 NOAJ July-December 2013, Vol 3, Issue 2, 38-40